Unveiling the Philosophical Essence of China's Century-Long Legal History Through the Lens of Traditional Historical Allusions, 1927-2020 (MINDEN Journal of History and Archaeology, 2025)
The historical philosophy of the rule of law in China encapsulates the intellectual heritage and practical experience of a century of legal evolution, rooted in the broader context of Chinese governance and state-building. This framework preserves the innovative legal thought of the New Democratic Revolution while integrating the legacies of socialist revolution and national modernization. Over time, it has dynamically evolved to support the construction of a legal system adapted to the demands of socialism with Chinese characteristics. Grounded in this legal philosophy, China has systematically advanced its socialist legal system, contributing to the theoretical foundation that underpins national governance and the broader goal of the Chinese Dream of national rejuvenation.This study provides an in-depth examination of the integration and reinterpretation of legal allusions from 1931 to 2020, tracing their impact on the trajectory of China's legal development. By exploring these historical references, the research highlights the enduring spirit of legal innovation and the key achievements in China’s rule of law construction. It further assesses the significance of the Third Plenary Session of the 20th Central Committee of the Communist Party of China in deepening legal reform and strengthening national governance. This analysis offers a comprehensive evaluation of both theoretical advancements and practical milestones in China’s legal evolution, emphasizing their long-term importance for the country's governance and its future trajectory.Keywords: Chinese Tradition; Historical Allusion; Historical Philosophy; History of the Rule of Law; Rule of Law